Modelling lung diffusion-perfusion limitation in mechanically ventilated SARS-CoV-2 patients - Miserocchi, Giuseppe; Rezoagli, Emanuele; Muñoz-Del-Carpio-Toia, Agueda; Paricahua-Yucra, Leydi Pamela; Zubieta-DeUrioste, Natalia; Zubieta-Calleja, Gustavo; Beretta, Egidio (Frontiers in Physiology, 2024)
This is the first study to describe the daytime evolution of respiratory parameters in mechanically ventilated COVID-19 patients. The data base refers to patients hospitalised in the intensive care unit (ICU) at Arequipa Hospital (Peru, 2335m) in 2021. In both survivors (S) and non survivors (NS) patients, a remarkable decrease in respiratory compliance was observed, revealing a proportional decrease in inflatable alveolar units. The S and NS patients were all hyperventilated and their SatO2 was maintained at >90%. However, while S remained normocapnic, NS developed progressive hypercapnia. We compared the efficiency of O2 uptake and CO2 removal in the air blood barrier relying on a model allowing to partition between diffusion and perfusion limitations to gas exchange.The decrease in O2 uptake was interpreted as diffusion limitation, while the impairment in CO2 removal was modelled by progressive perfusion limitation. The latter correlated with the increase in positive end-expiratory pressure (PEEP) and plateau pressure (Pplat), leading to capillary compression, increased blood velocity, and considerable shortening of the air-blood contact time.